Avaliação da compensação financeira como instrumento do desenvolvimento a oferta de saneamento básico - FERREIRA, Laysse Alves (2022)
The Hydroelectric Power Plants generate great environmental, economic and social consequences. Due to such non-mitigable consequences, financial compensation was instituted. The objective of this study was to analyze the compensatory transfers and their application in the sanitation supply in the municipalities affected by the UHE of Tucuruí-Pará. The methodological process began with a review of the literature, and secondary data were collected on digital platforms from the study area for the compensatory values received, water supply, sanitary sewage and solid waste, and data were organized into tables and (spreadsheets), in addition to the cartographic maps (ArcGis), to explain the results. It was verified that the coverage to the water supply obtained a timid growth in the years of 2000 to 2007, being that in 2015 all the indices of supply returned. Solid waste collections evolved in all municipalities, however, without adequate final destination. Of the seven municipalities analyzed, only in Tucuruí there is collection and treatment of sanitary sewage (13% of the population). In all municipalities there are large incidence of diseases related to lack of sanitation. In view of the above, it was concluded that there were no significant advances in the supply of sanitation in the municipalities studied.